SERCA2 regulates non-CF and CF airway epithelial cell response to ozone. - Shama Ahmad; David P Nichols; Matthew Strand; Raymond C Rancourt; Scott H Randell; Carl W White; Aftab Ahmad (PLoS ONE, 2011)
Calcium mobilization can regulate a wide range of essential functions of respiratory epithelium, including ion transport, ciliary beat frequency, and secretion of mucus, all of which are modified in cystic fibrosis (CF). SERCA2, an important controller of calcium signaling, is deficient in CF epithelium. We conducted this study to determine whether SERCA2 deficiency can modulate airway epithelial responses to environmental oxidants such as ozone. This could contribute to the pathogenesis of pulmonary exacerbations, which are important and frequent clinical events in CF. To address this, we used air-liquid interface (ALI) cultures of non-CF and CF cell lines, as well as differentiated cultures of cells derived from non-CF and CF patients. We found that ozone exposure caused enhanced membrane damage, mitochondrial dysfunction and apoptotic cell death in CF airway epithelial cell lines relative to non-CF. Ozone exposure caused increased proinflammatory cytokine production in CF airway epithelial cell lines. Elevated proinflammatory cytokine production also was observed in shRNA-mediated SERCA2 knockdown cells. Overexpression of SERCA2 reversed ozone-induced proinflammatory cytokine production. Ozone-induced proinflammatory cytokine production was NF-κB- dependent. In a stable NF-κB reporter cell line, SERCA2 inhibition and knockdown both upregulated cytomix-induced NF-κB activity, indicating importance of SERCA2 in modulating NF-κB activity. In this system, increased NF-κB activity was also accompanied by increased IL-8 production. Ozone also induced NF-κB activity and IL-8 release, an effect that was greater in SERCA2-silenced NF-κB-reporter cells. SERCA2 overexpression reversed cytomix-induced increased IL-8 release and total nuclear p65 in CFTR-deficient (16HBE-AS) cells. These studies suggest that SERCA2 is an important regulator of the proinflammatory response of airway epithelial cells and could be a potential therapeutic target.